Vocabulary puzzles grade 1 - School Zone Interactive (Grand Haven, Mich School Zone Interactive, 2005)
This program challenged children to recognize, pronounce, and spell words
Ages 5-6
System requirements for Windows: Pentium 166 MHz or faster processor; 32 MB RAM, 50 MB free disk space; Windows 95, 98 or higher; 640x480 16-bit color video, 16-bit sound card, 4x CD-ROM drive
1
Keywords: Vocabulary -- puzzles -- audiovisual; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs